2022
DOI: 10.1155/2022/4057215
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of High-Dose Vitamin C Infusion on Outcomes in Sepsis Requiring Mechanical Ventilation: A Double-Blind Randomized Controlled Trial

Abstract: Background. Critically ill patients have an increased requirement for vitamin C in sepsis and these patients have low levels of vitamin C. The researchers validated the efficacy of high-dose vitamin C intravenous infusion (IVI) in patients with sepsis requiring mechanical ventilation. Methods. Forty patients were randomly assigned to 2 groups (20 each) in a 1 : 1 ratio in accordance with the vitamin C treatment regimen: Group I (GI): patients received 1.5 g/6 h vitamin C in 50 ml of dextrose 5% in water (D5W) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 42 publications
(77 reference statements)
0
23
0
Order By: Relevance
“…Adverse effects of vitamin C were rare. Driny et al believed that vitamin C was safe, tolerable and would not cause patients withdraw from the study [35]. On the basis of this study, Fowler et al reported that different doses of vitamin C would not lead to any serious adverse events [7].…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…Adverse effects of vitamin C were rare. Driny et al believed that vitamin C was safe, tolerable and would not cause patients withdraw from the study [35]. On the basis of this study, Fowler et al reported that different doses of vitamin C would not lead to any serious adverse events [7].…”
Section: Discussionmentioning
confidence: 74%
“…We acknowledge some limitations. First of all, 10 RCTs [16, 23,24,27,[29][30][31][34][35][36] were all single center studies with small sample size, which may result in selective bias or introduce small sample effect, so as to obtain a large bene cial therapeutic effect conclusion. Second, RCTs in this meta-analysis used different doses of vitamin C. Most RCTs administered 1.5 g vitamin C every 6 hours or 25 mg/kg every 6 hours, whereas other RCTs administered 50 mg/kg every 6 hours or 200 mg/kg daily.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these results were based on analyses that did not consider multiple comparisons and should therefore be considered exploratory [ 6 ]. It has been reported that vitamin C reduces 28-day mortality and dosage and duration of norepinephrine in intermittent intervals [ 50 ], also reducing the risk of pulmonary morbidity and organ failure [ 51 ]. Lamontagne et al reported no statistical differences between placebo and supplemented group [ 50 ].…”
Section: Antioxidant Treatments In Sepsismentioning
confidence: 99%